Development of Flipchart Learning Media on the Material "The Beauty of Diversity in My Country" - Faiza Nur Fadillah Putri; Ana Nurhasanah; Muhammad Taufik (Universitas Pendidikan Indonesia Kampus Serang, 2023)
The learning media development is based on existing teaching materials that do not yet provide an overall picture of cultural diversity in Indonesia, and the methods given by teachers only assign some of the diversity. The urgency in the class has a high level of curiosity, but to see this diversity, the teacher only displays it through his device and gives it to students who ask questions, resulting in an uneven distribution of student activity. Therefore, the research aims to ascertain the steps for making flipchart learning media, the validity of experts, and students' responses to flipchart media. The research method was RD, using the ADDIE model, with material expert testing: curriculum, methods, language, and evaluation, and learning media expert testing in verbal, cover design, content design, and typography. The feasibility test was carried out by four lecturers of the Faculty of Teacher Training and Education. The validation results from the two validators' material experts obtained an average percentage of 94%, with the criteria being "very feasible." The two validators' learning media expert validation received 87.5%, with the criteria "very feasible." With the "very feasible" criteria, the overall average percentage of validators was 90.75%. For student responses, a percentage of 91.5% was attained, with the criteria being "very feasible." Based on the validation results of two material expert lecturers, two media expert lecturers, and the responses of class IV students, flipchart learning media could be described as "very suitable" for use in elementary schools and could enhance student activity.